2019
DOI: 10.1371/journal.pone.0219834
|View full text |Cite
|
Sign up to set email alerts
|

A cell-loss-free concave microwell array based size-controlled multi-cellular tumoroid generation for anti-cancer drug screening

Abstract: The 3D multi-cellular tumoroid (MCT) model is an in vivo -like, avascular tumor model that has received much attention as a refined screening platform for drug therapies. Several types of research have been efforted to improve the physiological characteristics of the tumor microenvironment (TME) of the in vivo -like MCTs. Size-controlled MCTs have received much attention for obtaining highly reproducible results in drug screening assays and achieving a homogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…For example, Liu et al used an ice lithography method carried out on superhydrophobic substrates to fabricate a quasi-spherical microwell chip 52 . Lee et al also made a concave microwell chip using a double PDMS casting procedure from the PMMA mold that was made by a laser carving machine 53 . In a creative and simple method, Kim et al fabricated a concave-bottomed microwell chip using the capillary action of liquid polymer on the pins of a computer CPU, which is achieved without expensive materials or complicated procedures 54 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, Liu et al used an ice lithography method carried out on superhydrophobic substrates to fabricate a quasi-spherical microwell chip 52 . Lee et al also made a concave microwell chip using a double PDMS casting procedure from the PMMA mold that was made by a laser carving machine 53 . In a creative and simple method, Kim et al fabricated a concave-bottomed microwell chip using the capillary action of liquid polymer on the pins of a computer CPU, which is achieved without expensive materials or complicated procedures 54 .…”
Section: Resultsmentioning
confidence: 99%
“…The tumoroids had dimensions that could provide tumor microenvironment. [13] In a study reported earlier the 80,000 μm 2 MCTS was obtained post 30 days of cell seeding, which the authors classified as the largest MCTS. [14] This size of tumoroids shows distinct zones of the heterogeneous population and the grape shaped 3D tumoroids recapitulates the nodal structure of solid tumors by mimicking various such aspects of nutrient gradient, [15] pH, [16] and Hypoxia.…”
Section: Tumoroid Formation Aided Through MDC Hydrogelmentioning
confidence: 98%
“…The fabrication process for the PDMS-based cell-lossfree (CLF) concave microwell array (1 mm microwell size, 225 wells/microwell array) was described in detail in our previous study [22]. The CLF concave microwell array was fabricated by using a 35 mm culture plate as the size slab.…”
Section: Cell Culture and Formation Of 3d Mcts-ecm Tumor Graftsmentioning
confidence: 99%
“…These MCT models are composed of nonmigrating cells, including an epithelial phenotype with apical-basal polarity by active cell-cell interactions based on the basement membrane. Our previous study also introduced the development of a CLF microwell array for the formation of robust MCTs using this array and suggested their usefulness through a drug response test [22]. However, to more accurately explain the therapeutic effect, it is necessary to consider cellular behavior, such as the motility of cancer cells through the ECM, which is a structural component constituting the in vivo TME, and the increase in drug resistance.…”
Section: Development Of a Macroscale 3d In Vitro Tumor Graft Model By...mentioning
confidence: 99%